Treatment of various degrees of white spot lesions using resin infiltration—in vitro study - Bassant A. Abbas; Eiman S. Marzouk; Abbas R. Zaher (Progress in Orthodontics, 2018)
Abstract Background This study was conducted to evaluate the efficiency of resin infiltration to improve the color of white spot lesions (WSLs) and to estimate the effect of different numbers of etching and resin infiltrant applications on the color change of WSLs with various depths. Ninety-six sound extracted premolars were subjected to acid attack inducing different depths of WSLs. Using a DIAGNOdent, teeth were divided into four main groups according to the depth of the WSLs: shallow enamel, deep enamel, shallow dentine, and deep dentine without cavitation. Then each of the main groups was subdivided into four groups: six teeth each with different protocols of resin infiltration as follows: 1 etching + 1 infiltrant application (EA), 1 etching + 2 infiltrant applications (EAA), 2 etchings + 1 infiltrant application (EEA), 2 etchings + 2 infiltrant applications (EEAA). Spectrophotometric analysis was measured at baseline (T0), after inducing the WSLs (T1), and following resin infiltration application (T2) for each group. Results In shallow enamel, EA produced the least mean color difference (1.62 ± 0.85), with high significant difference (P < 0.001), when compared with the clinically detectable threshold (ΔE = 3.7). While in deep enamel, EAA showed the least mean color change (1.95 ± 0.4), with P < 0.001 when compared with the critical value. Also, in shallow dentine, the least mean change was noticed with EAA (3.0 ± 0.45), with P < 0.001 when compared with the clinical color detection threshold. Furthermore, in deep dentine, EAA had the least mean difference (3.76 ± 0.6) but with no significant difference, when compared with the clinically detectable threshold. Conclusions As the WSL got deeper, the color of the lesion became more clinically visible. In shallow enamel, the best treatment option was one etching with one resin infiltrant application. For deep enamel and shallow dentine, one etching with two applications of infiltrant gave the best lesion masking. In deep dentine, it is advisable to perform one etching with two infiltration steps, taking in consideration that all deep dentine lesions without cavitation were partially masked, remained clinically detectable, and might require more invasive restorative procedures.